The decision to initiate dialysis in children and adolescents - Greenbaum, Larry; Schaefer, Franz (Pediatric dialysis, 2004)
The initiation of chronic dialysis in a child is a dramatic event for the patient and family. Dialysis begins a new and often frightening stage of the child’s medical care. The urgent need to begin dialysis is obvious in some instances, such as after a bilateral nephrectomy or in the child with uremic pericarditis. These are absolute indications for initiating dialysis. In other patients the timing of dialysis initiation is less clear. The pediatric nephrologist integrates a great deal of information-laboratory data, clinical impressions, and psychosocial issues-in order to reach a decision regarding the timing of dialysis initiation. An assessment of renal function is usually a critical part of this process. In addition, a variety of clinical and laboratory findings are relative indications for commencing chronic dialysis. Some of these relative indications can be managed with medications and dietary counseling, but this approach is not always successful, necessitating the initiation of dialysis.
Gesehen am 29.01.2021